Proyecto de factibilidad para la creación de una empresa productora y comercializadora de vino de membrillo en el cantón el pangui, provincia de Zamora Chinchipe para el año 2015 - Guayllas Sarango, Luz Delicia (2016)
Present it thesis registered as a legitimate real estate property I Project of feasibility for the creation of a productive company and marketer of wine of quince at the canton The Pangui, Zamora Chinchipe's province for the year 2015 The Pangui is focused toward the sostenibilidad of the productive children of the canton and Zamora's province. His general objective is to determine the commercial viability to implement the present project; Considering that this fruit has a mass production at all the province and in a minute does not exist no company at the canton The Pangui than this once the industrialization was dedicated of the quince. In this sense and on the basis of the presented objective, he turned to the use of fact-finding methods, I eat such: The inductive, deductive, statistical and scientific. In addition to the application of fact-finding techniques like the direct observation and the application of opinion polls to 355 people's sign inhabitants at the canton The Pangui. Once the sign was obtained one proceeded to the market research through opinion polls with which it was determined than exists an effective demand for consumption of wine of quince of 67,579 bottles, in front of an offer of 28,416 wine bottles of fruits offered at the sector, determined that way an unsettled request of 39,163 bottles of the mentioned product. With these background and with the appropriate certainty, sustended at the objective entrepreneurial clearings and industrials and in front of the scarcity of financial resources, but for the sake of improving the standards of living of the productive children of this sector; With the present work it is demonstrated agreed that the execution of the present project is priority and un postponable.